Improving expression of recombinant human IGF‐1 using IGF‐1R knockout CHO cell lines. Issue 5 (18th January 2016) - Romand, Sandrine; Jostock, Thomas; Fornaro, Mara; Schmidt, Joerg; Ritter, Anett; Wilms, Burkhard; Laux, Holger
ABSTRACT: Chinese Hamster Ovary (CHO) cells are widely used for the large‐scale production of recombinant biopharmaceuticals. However, attempts to express IGF‐1 (a mutated human Insulin‐like growth factor 1 Ea peptide (hIGF‐1Ea mut)) in CHO cells resulted in poor cell growth and low productivity (0.1–0.2 g/L). Human IGF‐1 variants negatively impacted CHO cell growth via the IGF‐1 receptor (IGF‐1R). Therefore knockout (KO) of the IGF‐1R gene in two different CHO cell lines as well as knockdown (KD) of IGF‐1R in one CHO cell line were performed. These cell line engineering approaches decreased significantly the hIGF‐1 mediated cell growth inhibition and increased productivity of both KO CHO cell lines as well as of the KD CHO cell line. A productivity increase of 10‐fold at pool level and sevenfold at clone level was achieved, resulting in a titer of 1.3 g/L. This data illustrate that cell line engineering approaches are powerful tools to improve the yields of recombinant proteins which are difficult to produce in CHO cells. Biotechnol. Bioeng. 2016;113: 1094–1101. © 2015 Wiley Periodicals, Inc. Abstract : The authors demonstrated that human IGF‐1 variants (hIGF‐1) were difficult to express in CHO cell lines due to host cell IGF‐1R mediated cell growth inhibition, resulting in low productivity and downregulation of mitochondrial encoded transcripts. Using zinc‐finger‐nuclease technique they knocked out IGF‐1R, resulting in decreased hIGF‐1 mediated cell growth inhibition, elimination of mitochondrial encoded transcripts downregulation, and a 7–10 fold productivity increase. This study illustrates that genetic engineering approaches are powerful tools to improve the yields of recombinant proteins which are difficult to be produced.